Language, Vernacular Discourse and Nationalisms Uncovering the Myths of Transnational Worlds - Ndhlovu, Finex (Springer International Publishing, 2018)
'This pathbreaking study shows that anti-(African) immigrant rhetoric is part of a widespread ethno-centric political vernacular and demonstrates how these negative ethnic stereotypes have arisen from severe economic inequalities and the uneven development. This is a deeply grounded analysis of local-level ethno-centrism which places the issue firmly in the context of the local and global political economy. It deserves a wide readership.' -Don Robotham, City University of New York, USA 'This is a must read not only for scholars in the emerging field of the sociolinguistics of (de)coloniality and globalisation, but also those interested in language and the political and ideological formations in the construction of nation-states in South Africa, Zimbabwe and Australia.' -Felix Banda, University of the Western Cape, South Africa 'Professor Finex Ndhlovu's is an important voice in the field of language studies. His trade mark being the careful but consistent contextualization of knotty language questions within the broader terrain of equally complex identitarian politics, while at the same time bringing into creative dialogue African and non-African empirical case studies to demonstrate the global implications and resonance of his research findings.' -Sabelo J Ndlovu-Gatsheni, University of South Africa This book examines the linguistic and discursive elements of social and economic policies and national political leader statements to read new meanings into debates on border protection, national sovereignty, immigration, economic indigenisation, land reform and black economic empowerment. It adds a fresh angle to the debate on nationalisms and transnationalism by pushing forward a more applied agenda to establish a clear and empirically-based illustration of the contradictions in current policy frameworks around the world and the debates they invite. The author's novel vernacular discourse approach contributes new points of method and interpretation that will advance scholarly conversations on nationalisms, transnationalism and other forms of identity imaginings in a transient world. Finex Ndhlovu is Associate Professor of Language in Society at the University of New England, Australia, Distinguished Visiting Professor at the Graduate Center, City University of New York, USA, and Visiting Research Professor at the University of South Africa. .